The Power of the Law - the Law of Power: On the Significance of Canon Law for Issues of Power in the Church - Hahn, Judith (Concilium, 2020)
As in any legal system, power plays an essential role in canon law, in two respects. The power of law indicates the central significance of law in building and shaping society. As the law of power, it puts forward rules that create authority and assign competences within a community governed by law. The authority (power) thus created, however, needs legitimation if it is to be respected in the community. This in turn takes place in the modern era first and foremost through law: power counts as legitimate when it is limited by law. The fact that this rule of law has been undermined in the Church is currently putting canon law under pressure and raising questions about its legitimacy. If we are going to talk about power and law, three things need to be clarified first. What power means and what law means has to be established, and a connection has to be made between power and law. This is made more difficult by the fact that power is an extremely controversial concept in the social sciences;1 the sociologist Steven Lukes calls it an "essentially contested concept".2 To talk about power demands a choice for one of the developed concepts of power. For a study of the connection between power and law the analysis of power produced by Niklas Luhmann has the advantage not only that Luhmann used a concept in which power and law related to each other, but also that he established a strong relationship between the two.